Organic Chemistry from Retrosynthesis to Asymmetric Synthesis - Šunjić, Vitomir; Petrović Peroković, Vesna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book connects a retrosynthetic or disconnection approach with synthetic methods in the preparation of target molecules from simple, achiral ones to complex, chiral structures in the optically pure form. Retrosynthetic considerations and asymmetric syntheses are presented as closely related topics, often in the same chapter, underlining the importance of retrosynthetic consideration of target molecules neglecting stereochemistry and equipping readers to overcome the difficulties they may encounter in the planning and experimental implementation of asymmetric syntheses. This approach prepares students in advanced organic chemistry courses, and in particular young scientists working at academic and industrial laboratories, for independently solving synthetic problems and creating proposals for the synthesis of complex structures.
Foreword -- Introduction -- Retrosynthetic Analysis of compounds with one functional group -- Stereoisomers and stereoselective reactions - "Departure to the third dimension" -- Disconnection by participation of two functional groups -- "Illogical" disconnections with participation of two groups -- Specific synthetic methodologies -- Retrosynthetic consideration of heterocyclic structures -- Retrosynthetic consideration of complex biologically active molecules -- Abbreviations and acronymes -- Subject index.
Keywords: Chemistry, Organic; Biotechnology; Chemistry, Technical; Organic Chemistry; Chemical Bioengineering; Industrial Chemistry